Prediction of high-K isomeric states in transactinide nuclei close to N=162 - Prassa, V.; Lu, B.-N.; Niksic, T.; Ackermann, D.; Vretenar, D. (HNPS Advances in Nuclear Physics, 2019)
Transactinide nuclei around neutron number N=162 display axially deformed equilibrium shapes. In the present study we are particularly interested in the occurrence of high-K isomers in the axially deformed isotopes of Rf (Z=104), Sg (Z=106), Hs (Z=108), and Ds (Z=110), with neutron number N=160-166 and the effect of the N=162 closure on the structure and distribution of two-quasiparticle (2qp) states. The evolution of high-K isomers is analyzed in a self-consistent axially symmetric relativistic Hartree-Bogoliubov calculation using the blocking approximation with time-reversal symmetry breaking.